Silica sol modified chromium-iron slag aggregate and preparation method thereof
Patent Information
- Application Number
- CN202410392628.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-02
AI Technical Summary
[0005]技术问题:本发明的目的在于提供一种硅溶胶改性铬铁渣骨料及其制备方法,该方法成本低廉、绿色环保、工艺简单,该方法解决了铬铁渣粗糙多孔吸水率高的问题,使得改性后的铬铁渣骨料表面平滑,孔隙率、吸水率显著降低,从而优化新拌混凝土浆体的工作性,提高混凝土的力学性能和耐久性
[0022]1)本方法以稻壳灰为原料制备纳米硅溶胶,摒弃了传统金属醇盐作硅源带来的毒性,有效地缓解了环境压力,且工艺对设备复杂度和精度要求不高,容易实现工业化生产;
Smart Images

Figure CN118183760B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a silica sol-modified ferrochrome slag aggregate and its preparation method, belonging to the field of building materials technology. Background Technology
[0002] High-carbon ferrochrome slag is a byproduct of ferrochrome alloy smelting. Statistics show that as of last year, my country's annual high-carbon ferrochrome smelting waste slag exceeded 8.4 million tons. Traditional disposal methods—simple landfilling or stockpiling—result in a significant waste of land resources and pose environmental risks: the leached chromium in the slag... 6+ It is highly toxic, affects the growth of plants and animals, and long-term exposure can lead to skin and respiratory diseases. Therefore, the resource utilization of ferrochrome slag is imperative.
[0003] Ferrochrome slag is an inorganic non-metallic material, with magnesium-based olivine and spinel as its main phases. Based on the cooling method, it can be simply divided into water-cooled and air-cooled ferrochrome slag. Water-cooled slag cools rapidly, has fine particles and numerous pores, and mostly consists of a metastable glassy phase, which affects its strength; while air-cooled slag typically has larger and coarser particles, with a predominance of crystals in its phase composition. Because ferrochrome slag contains a large amount of silicon and aluminum, standardized tailings, after adjusting the component ratios, can be widely used in metallurgy, ceramics, and refractory materials. In the construction industry, there are precedents for using ferrochrome slag as a mineral admixture and aggregate. Through the analysis of Cr... 6+ The leaching rate can be monitored and controlled to ensure compliance with local environmental standards and regulations. However, due to the low active silica content and overall inertness of ferrochrome slag, its application as an inert fine-particle filler and auxiliary cementitious material (SCM) has yielded limited success. Currently, there are practical examples demonstrating the potential of ferrochrome slag to completely replace natural sand and gravel as aggregate. It should be noted that its porous morphology and high water absorption rate may affect the durability and strength of the material.
[0004] Nano-silica sol is a colloidal solution of nano-sized SiO2 stably dispersed in a medium, possessing excellent adsorption properties and a large specific surface area. Its mesoporous structure provides reactive sites. Furthermore, due to the good permeability of silica sol to cement-based materials, the incorporated colloidal particles can act as fillers. Additionally, considering the compatibility of silica sol with ferrochrome slag, and the Ca in calcium acrylate... 2+ It can rapidly combine with the active Si-OH groups of cement-based materials to form CSH gel, effectively sealing pores and reducing water absorption. Furthermore, under the action of initiators and crosslinking agents, calcium acrylate forms a polyacrylate skeleton structure, further improving the compressive and flexural strength of the aggregate. Summary of the Invention
[0005] Technical Problem: The purpose of this invention is to provide a silica sol-modified ferrochrome slag aggregate and its preparation method. This method is low-cost, environmentally friendly, and simple. It solves the problem of rough, porous ferrochrome slag with high water absorption, resulting in a smooth surface and significantly reduced porosity and water absorption of the modified ferrochrome slag aggregate. This optimizes the workability of fresh concrete paste and improves the mechanical properties and durability of concrete.
[0006] Technical solution: A silica sol-modified ferrochrome slag aggregate is prepared by immersing ferrochrome slag aggregate in nano-silica sol and soaking it thoroughly, then adding modifiers, crosslinking agents, initiators and accelerators to react and strengthen the aggregate, and finally curing and drying it for later use; the nano-silica sol is obtained by using rice husk ash as raw material through the sol-gel method, acid washing, reaction with NaOH, adjusting the pH value to 8-10 with acid, and then aging.
[0007] During the pickling process, the pH value needs to be adjusted to 4-5, and the acid used is nitric acid or acrylic acid.
[0008] The modifier is calcium acrylate, added at 10wt%–20wt% of the nano-silica sol solution. The crosslinking agent is tris(3-aziridinyl)propionate (molecular formula C... 20 H 33 The initiator is potassium persulfate (N3O7), and the accelerator is triethanolamine.
[0009] The mass ratio of modifier, crosslinking agent, accelerator and initiator is 100:5:1:2.5.
[0010] The method for preparing the silica sol-modified ferrochrome slag aggregate includes the following steps:
[0011] 1) The rice husk ash was acid-washed using the sol-gel method to remove metal ions. After drying, NaOH solution was added, stirred, and filtered to obtain a brown sodium silicate solution.
[0012] 2) After adjusting the pH of the water glass solution to 8-10 by acid titration, the nano-silica sol gel was obtained by aging and centrifugation, dried and ground for later use;
[0013] 3) Prepare a silica sol solution from nano-silica sol and disperse it under an ultrasonic cleaner, then immerse the ferrochrome slag aggregate in it and soak it thoroughly;
[0014] 4) Add modifiers and crosslinking agents to the fully soaked solution to strengthen the aggregate, and add a small amount of initiator and accelerator to accelerate the reaction;
[0015] 5) After curing, the modified aggregate is dried and solidified for later use.
[0016] The amount of NaOH mentioned in step 1) is 0.6 to 0.8 mol.
[0017] The aging time required for the aging and centrifugation step described in step 2) is 2 to 3 days, and the centrifugation speed is 3500 to 4000 rpm.
[0018] Step 3) describes the dispersion of a certain mass fraction of nano-silica sol solution under an ultrasonic cleaner. The ultrasonic cleaning time is 20-30 minutes, the ultrasonic frequency is 30-40 kHz, and the nano-silica sol solution is 5 wt-10 wt%.
[0019] The curing conditions described in step 4) are 20±2℃, relative humidity of 95%, and curing time of 3 days.
[0020] The drying temperature described in steps 1), 2), and 4) is 110–140°C, and the drying time is 12–18 h.
[0021] Beneficial effects:
[0022] 1) This method uses rice husk ash as raw material to prepare nano-silica sol, which eliminates the toxicity of traditional metal alkoxides as silicon sources, effectively alleviates environmental pressure, and the process does not require high equipment complexity and precision, making it easy to achieve industrial production.
[0023] 2) The nano-silica sol used in this method has stronger permeability than nano-SiO2 powder, making it easier to achieve uniform dispersion in the medium and thus enabling sufficient contact with the aggregate to be modified. The excess nano-silica sol solution, while reacting with calcium acrylate, not only achieves a pore-sealing effect but also retains active nano-SiO2 particles on the surface and inside, playing a crucial role in interfacial bonding and microstructure optimization. Simultaneously, under the action of the crosslinking agent, the skeleton structure formed by calcium acrylate further enhances the overall mechanical properties of the aggregate, allowing its reinforcing effect in concrete to be fully realized.
[0024] 3) The modified chromium slag aggregate has reduced porosity and water absorption, a smoother surface, and relatively stable internal structure. When using the modified aggregate to form concrete, the water requirement is significantly reduced, and the workability of the freshly mixed paste is optimized. This results in a significant increase in concrete strength, a decrease in the chloride ion diffusion coefficient, and an optimized aggregate-paste interface structure, effectively improving the mechanical properties and durability of the concrete. Attached Figure Description
[0025] Figure 1 The 28-day chloride ion diffusion coefficients are for the modified chromium slag aggregate concrete of Examples 1-5 and the control example.
[0026] Figure 2 The 28-day chloride ion carbonation depth of the modified chromium ferro slag aggregate concrete in Examples 1-5 and the control example. Detailed Implementation
[0027] The present invention will now be described in detail with reference to specific embodiments.
[0028] In the embodiments of this invention, the coarse and fine aggregates used are obtained by crushing and screening air-cooled high-carbon ferrochrome slag. The particle size range of the coarse aggregate is 5-20 mm; the particle size range of the fine aggregate is 0.75-5 mm.
[0029] This invention discloses a method for preparing silica sol-modified ferrochrome slag aggregate, which includes the following steps:
[0030] 1) Rice husk ash was acid-washed using the sol-gel method to remove metal ions. After drying, NaOH solution was added, stirred, and filtered to obtain a brown sodium silicate solution.
[0031] 2) After adjusting the pH of the water glass solution to 8-10 by acid titration, the nano-silica sol gel was obtained by aging and centrifugation, dried and ground for later use;
[0032] 3) Prepare a certain fraction of silica sol solution with nano silica sol and disperse it under an ultrasonic cleaner, then immerse the chromium ferrochrome slag aggregate in it and soak it thoroughly;
[0033] 4) Add modifiers and crosslinking agents to the fully soaked solution to strengthen the aggregate, and add a small amount of initiator and accelerator to accelerate the reaction.
[0034] 5) After curing in a specific environment, the modified aggregate is dried and solidified for later use.
[0035] in:
[0036] In the pickling process described in step 1), the pH value needs to be adjusted to 4-5, and the acid used is nitric acid or acrylic acid.
[0037] The amount of NaOH mentioned in step 1) is 0.6 to 0.8 mol.
[0038] The aging time required for the aging and centrifugation step described in step 2) is 2 to 3 days, and the centrifugation speed is 3500 to 4000 rpm.
[0039] Step 3) describes the dispersion of a certain mass fraction of nano-silica sol solution under an ultrasonic cleaner. The ultrasonic cleaning time is 20-30 minutes, the ultrasonic frequency is 30-40 kHz, and the nano-silica sol solution is 5 wt-10 wt%.
[0040] The modifier mentioned in step 4) is calcium acrylate, and its addition amount is 10wt% to 20wt% of the dispersed nano-silica sol solution. The crosslinking agent is tris(3-aziridinyl)propionate (molecular formula C). 20 H 33The modifier is N3O7, the initiator is potassium persulfate, the accelerator is triethanolamine, and the ratio of modifier, crosslinking agent, accelerator and initiator is 100:5:1:2.5.
[0041] The curing conditions described in step 4) are 20±2℃, relative humidity of 95%, and curing time of 3 days.
[0042] The drying temperature in steps 1), 2), and 4) is 110–140°C, and the drying time is 12–18 h.
[0043] Example 1:
[0044] A method for preparing silica sol-modified ferrochrome slag aggregate, the method comprising the following steps:
[0045] 1) Prepare a nano-silica sol solution with a mass fraction of 5% using water as a solvent by preparing nano-silica sol particles made from rice husk ash, and ultrasonically disperse it in an ultrasonic cleaner with a frequency of 40KHz for 20min. Soak coarse and fine aggregates of chromium slag in the ultrasonically treated solution for 3 days.
[0046] 2) After soaking, open the sealed lid and add calcium acrylate at a mass fraction of 20% of the soaking solution. Based on the mass of calcium acrylate added, add tris(3-aziridinyl)propionate, triethanolamine, and potassium persulfate in a ratio of 100:5:1:2.5, mix well, and let stand.
[0047] 3) Place the fully impregnated chromium slag aggregate into a standard curing room at 20±2℃ and 95% relative humidity for curing. After 3 days, remove it and dry it for later use.
[0048] 4) Take 312 parts of P·II52.5 cement, 156 parts of metakaolin, 748 parts of modified ferrochrome slag fine aggregate, including 343 parts of 5-10mm modified ferrochrome slag coarse aggregate, including 685 parts of 10-20mm modified ferrochrome slag coarse aggregate, 151 parts of water, and 4.6 parts of water-reducing agent.
[0049] Example 2:
[0050] A method for preparing silica sol-modified ferrochrome slag aggregate, the method comprising the following steps:
[0051] 1) Prepare a nano-silica sol solution with a mass fraction of 5% using water as a solvent by preparing nano-silica sol particles made from rice husk ash, and ultrasonically disperse it in an ultrasonic cleaner with a frequency of 40KHz for 20min. Soak coarse and fine aggregates of chromium slag in the ultrasonically treated solution for 3 days.
[0052] 2) After soaking, open the sealed lid and add calcium acrylate at a mass fraction of 20% of the soaking solution. Based on the mass of calcium acrylate added, add tris(3-aziridinyl)propionate, triethanolamine, and potassium persulfate in a ratio of 100:5:1:2.5, mix well, and let stand.
[0053] 3) Place the fully impregnated chromium slag aggregate into a standard curing room at 20±2℃ and 95% relative humidity for curing. After 3 days, remove it and dry it for later use.
[0054] 4) Take 312 parts of P·II52.5 cement, 156 parts of metakaolin, 799 parts of chromium slag fine aggregate, 326 parts of 5-10mm chromium slag coarse aggregate, of which 651 parts are 10-20mm chromium slag coarse aggregate, 151 parts of water, and 4.6 parts of water-reducing agent.
[0055] Example 3:
[0056] A method for preparing silica sol-modified ferrochrome slag aggregate, the method comprising the following steps:
[0057] 1) Prepare a nano-silica sol solution with a mass fraction of 5% using water as a solvent by preparing nano-silica sol particles made from rice husk ash, and ultrasonically disperse it in an ultrasonic cleaner with a frequency of 40KHz for 20min. Soak coarse and fine aggregates of chromium slag in the ultrasonically treated solution for 3 days.
[0058] 2) After soaking, open the sealed lid and add calcium acrylate at a mass fraction of 20% of the soaking solution. Based on the mass of calcium acrylate added, add tris(3-aziridinyl)propionate, triethanolamine, and potassium persulfate in a ratio of 100:5:1:2.5, mix well, and let stand.
[0059] 3) Place the fully impregnated chromium slag aggregate into a standard curing room at 20±2℃ and 95% relative humidity for curing. After 3 days, remove it and dry it for later use.
[0060] 4) Take 312 parts of P·II52.5 cement, 156 parts of metakaolin, 799 parts of chromium slag fine aggregate, 326 parts of 5-10mm chromium slag coarse aggregate, of which 651 parts are 10-20mm chromium slag coarse aggregate, 151 parts of water, and 4.6 parts of water-reducing agent.
[0061] Example 4:
[0062] A method for preparing silica sol-modified ferrochrome slag aggregate, the method comprising the following steps:
[0063] 1) Prepare a nano-silica sol solution with a mass fraction of 5% using water as a solvent by preparing nano-silica sol particles made from rice husk ash, and ultrasonically disperse it in an ultrasonic cleaner with a frequency of 40KHz for 20min. Soak coarse and fine aggregates of chromium slag in the ultrasonically treated solution for 3 days.
[0064] 2) After soaking, open the sealed lid and add calcium acrylate at a mass fraction of 20% of the soaking solution. Based on the mass of calcium acrylate added, add tris(3-aziridinyl)propionate, triethanolamine, and potassium persulfate in a ratio of 100:5:1:2.5, mix well, and let stand.
[0065] 3) Place the fully impregnated chromium slag aggregate into a standard curing room at 20±2℃ and 95% relative humidity for curing. After 3 days, remove it and dry it for later use.
[0066] 4) Take 312 parts of P·II52.5 cement, 156 parts of metakaolin, 748 parts of fine aggregate of ferrochrome slag, 343 parts of coarse aggregate of 5-10mm ferrochrome slag, of which 685 parts are coarse aggregate of 10-20mm ferrochrome slag, 151 parts of water, and 4.6 parts of water-reducing agent.
[0067] Example 5:
[0068] A method for preparing silica sol-modified ferrochrome slag aggregate, the method comprising the following steps:
[0069] 1) Prepare a nano-silica sol solution with a mass fraction of 5% using water as a solvent by preparing nano-silica sol particles made from rice husk ash, and ultrasonically disperse it in an ultrasonic cleaner with a frequency of 40KHz for 20min. Soak coarse and fine aggregates of chromium slag in the ultrasonically treated solution for 3 days.
[0070] 2) After soaking, open the sealed lid and add calcium acrylate at a mass fraction of 20% of the soaking solution. Based on the mass of calcium acrylate added, add tris(3-aziridinyl)propionate, triethanolamine, and potassium persulfate in a ratio of 100:5:1:2.5, mix well, and let stand.
[0071] 3) Place the fully impregnated chromium slag aggregate into a standard curing room at 20±2℃ and 95% relative humidity for curing. After 3 days, remove it and dry it for later use.
[0072] 4) Take 312 parts of P·II52.5 cement, 156 parts of metakaolin, 799 parts of chromium slag fine aggregate, 326 parts of 5-10mm chromium slag coarse aggregate, of which 651 parts are 10-20mm chromium slag coarse aggregate, 151 parts of water, and 4.6 parts of water-reducing agent.
[0073] Comparison Example
[0074] This comparative example is C60 concrete, made from the following raw materials in parts by weight: 312 parts of P·II52.5 cement, 156 parts of metakaolin, 799 parts of unmodified ferrochrome slag fine aggregate, of which 326 parts are 5-10mm unmodified ferrochrome slag coarse aggregate, 651 parts are 10-20mm unmodified ferrochrome slag coarse aggregate, 151 parts of water, and 4.6 parts of water-reducing agent.
[0075] First, the cement, metakaolin, and other powdered materials, along with ferrochrome slag coarse aggregate, described in Examples 1-5 and the comparative example, are added to a horizontal mixer and mixed evenly. Then, a portion of the mixing water is added and stirred for 2 minutes until the slurry becomes viscous. Fine aggregate is then slowly added and mixing continues. Next, the remaining mixing water and water-reducing agent are added and stirred for 3 minutes. After the slurry is evenly mixed, it is poured into layers, molded, vibrated, and covered with a film. After 24 hours, it is demolded and placed in a standard curing room.
[0076] The mechanical properties and durability of the concrete prepared in Examples 1-5 were superior to those of the control example, with compressive strength growth rates ranging from 3.1% to 25.3% and flexural strength growth rates ranging from 3.8% to 41.8%. The chloride ion diffusion coefficient and carbonation layer depth were significantly reduced, demonstrating that the modified chromium ferrophosphate aggregate significantly improved the mechanical properties and durability of concrete.
[0077] Table 1. Workability and mechanical properties of modified ferrochrome slag concrete
[0078]
[0079] The above description is merely an application embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any variations and substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the protection scope of the present invention.
Claims
1. A silica sol-modified ferrochrome slag aggregate, characterized in that, Ferrochromate slag aggregate is immersed in nano-silica sol and fully soaked. Then, modifiers, crosslinking agents, initiators, and accelerators are added to react and strengthen the aggregate. Finally, it is cured, dried, and solidified for later use. The nano-silica sol is obtained by acid washing rice husk ash as raw material using the sol-gel method, followed by reaction with NaOH, and then adjusting the pH value to 8-10 with acid before aging. The modifier is calcium acrylate, and the amount added is 10 wt%-20 wt% of the nano-silica sol solution. The initiator is potassium persulfate, and the accelerator is triethanolamine. The mass ratio of modifier, crosslinking agent, accelerator, and initiator is 100:5:1:2.
5. During the acid washing process, the pH value needs to be adjusted to 4-5, and the acid used is nitric acid or acrylic acid.
2. The method for preparing the silica sol-modified ferrochrome slag aggregate according to claim 1, characterized in that, Includes the following steps: 1) Rice husk ash was acid-washed using the sol-gel method to remove metal ions. After drying, NaOH solution was added, stirred, and filtered to obtain a brown sodium silicate solution. 2) After adjusting the sodium silicate solution to pH 8-10 by acid titration, nano-silica sol gel was obtained by aging and centrifugation, then dried and ground for later use; 3) The nano-silica sol gel was prepared into a nano-silica sol solution and dispersed under an ultrasonic cleaner, and then the chromium ferrochrome slag aggregate was immersed in and fully soaked; the dispersion time of the ultrasonic cleaner was 20-30 min, the ultrasonic frequency was 30-40 kHz, and the nano-silica sol solution was 5 wt%-10 wt%; 4) Add modifiers and crosslinking agents to the fully soaked solution to strengthen the aggregate, and add a small amount of initiator and accelerator to accelerate the reaction; 5) After curing, the modified aggregate is dried and solidified for later use.
3. The method as described in claim 2, characterized in that: The amount of NaOH mentioned in step 1) is 0.6 to 0.8 mol.
4. The method as described in claim 2, characterized in that: The aging time required for the aging and centrifugation step described in step 2) is 2 to 3 days, and the centrifugation speed is 3500 to 4000 rpm.
5. The method as described in claim 2, characterized in that: The curing conditions described in step 5) are 20±2℃, relative humidity of 95%, and curing time of 3 days.
6. The method as described in claim 2, characterized in that: The drying temperature described in steps 1), 2), and 5) is 110–140°C, and the drying time is 12–18 hours.
Citation Information
Patent Citations
Organic inorganic nanometer composite hybrid waterproof leak stopping gel, and preparation method thereof
CN109180870A
Recycled coarse aggregate modified by silica sol as well as preparation method and application of recycled coarse aggregate
CN116947355A
Method for preparing silicon dioxide aerogel by normal pressure drying method using rice hull ash as raw material
CN1669921A